Uji In Vivo Elaeocarpus sphaericus Schum terhadap Kadar Gula Darah dan Struktur Jaringan Testis, Pankreas, dan Ginjal - Cicilia Novi Primiani; Pujiati Pujiati; Mohammad Arfi Setiawan (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Genitri plant (Elaeocarpus sphaericus Schum) has a complex chemical compound that has the potential to lower blood sugar levels. The purpose of this study was to analyze in vivo blood sugar levels and changes in tissue structure of the pancreas, testes seminiferous tubules, and sucrose-induced kidneys. The study used an experimental approach, 24 male Mus musculus mice were grouped into 4 treatment groups. Negative control (P0), positive control giving sucrose at a dose of 1.125 mg/g (P1); Sucrose induction treatment was at a dose of 1.125 mg/g and Gintri seed simplicia was at a dose of 1.300 mg/g (P2). Experimental animals before being induced by sucrose were fasted for 2 hours. Sucrose induction was carried out for 5 days, the experimental animals were given food and drink ad libitum. Checking blood sugar levels every 4 hours through the tail vein. Blood sugar levels of experimental animals P2 and P3 were 126 mg/ each followed by administration of a solution of genitri seeds and fruit for 36 days, every 6 days data was collected on blood sugar levels. On the 37th day, dislocation, surgery and organ harvesting of the testes, pancreas and kidneys were carried out, and preparation of HE staining tissue was made. Data analysis using One Way Anova. The results showed that sucrose induction reduced the diameter of the islets of Langerhans, increased the diameter of the seminiferous tubules of the testes, and reduced the diameter of the glomerulus of the kidney. Giving genitri seeds and fruit lowers blood sugar levels, affects the tissue structure of the pancreas, testes, and glomerulus. The F value of the diameter of the pancreatic islets of Langerhans 16,662; testicular seminiferous tubule diameter 13,433; Glomerular diameter 28,958.